Cometabolic degration of trichloroethylene (TCE) and 1,2-dichloroethane (1,2-DCA) in nitrification systems - Kocamemi, Bilge Alpaslan. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2005., 2005)
Public concern for the environment has taken on a new prominence with wastemanagement becoming a priority. As a consequence, new and environmental friendlymethods for pollutant degradation are vastly investigated. Advanced Oxidation Processes, involving ozonolysis, photolysis, electron beams and ultrasonic irradiation have beenidentified as viable alternatives to such research. In recent years, chemistry with ultrasoundwaves has become a method of interest among other Advanced Oxidation Processes,owing to the extreme conditions generated during acoustic cavitation. These extremes are such that water molecules are fragmented into radical species, such as the hydroxyl radical,which is the most powerful chemical oxidant ever known.The dissertation presented herein is about the investigation of advanced oxidationtechniques particularly, ultrasound for the remediation of water contaminated with bacterial and organic constituents. The method of study involved the application of threeultrasonic frequencies under various ambient conditions on infected water samples andsynthetic effluents containing phenol and phenolic derivatives. Reactor effluents weremonitored for assessing the reduction in bacterial density and phenolic concentration. The results were evaluated with the aim of optimizing process parameters anddetermining the reaction kinetics. Moreover, the study with phenol covered comparison ofultrasonic decay with that of ozonolysis and assessing impacts of combined ultrasound,ozone and UV applications. It was found that the efficiency of bacterial decay under 20 kHz ultrasonicirradiation could be enhanced by the addition of solid catalysts such as activated carbon,metallic zinc, ceramic beads. The reaction kinetics was found to represent that of chemicaldisinfection with chlorine. The degradation of phenol was found to proceed with maximum efficiency under300 kHz irradiation at acidic pH and ultrasound rendered detoxification of water samplesvalong with phenol degradation, although mineralization was not effective. Combination ofultrasound with ozone and UV irradiation was found to induce synergistic effects as a consequence of the enhancement in the mass transfer rate of ozone and photolysis ofultrasound-induced hydrogen peroxide to generate excess hydroxyl radicals.
Keywords: Nitrification.; Organochlorine compounds.; Trichloroethylene.; Dichloroethylene.